Comparative Assessment of Antidiabetic Properties of Aqueous Extract and its Silver Nanoparticles from Vernonia amygdalina (ASTERACEAE) - Johnson, Ekarika C.; Ebong, Aniekan S.; Ejinwa, Confidence G.; Eseyin, Olorunfemi A. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2024)
Background: Diabetes poses significant challenges globally, with modern drug costs and side effects often outweighing their benefits, leading to therapeutic failures. Natural sources, like Vernonia amygdalina (bitter-leaf), are being explored for their potential in diabetes management. This study compared the anti-diabetic effects of aqueous extract and nano-particles from V. amygdalina, using metformin as a benchmark. Methods: The phytochemicals were analyzed quantitatively and qualitatively using standard methods. The anti-diabetic activities were assayed using glucose uptake by yeast method and the percentage of glucose uptakes by yeast was calculated. Results: Phytochemical analysis identified saponins, tannins, alkaloids, phenols, and flavonoids in the plant, quantified as 0.156%, 0.013%, 0.022%, 0.003%, and 0.069%, respectively. Glucose uptake assays using yeast demonstrated enhanced uptake with silver nano-particles of the extract, particularly at 5mg/ml AgNPs, which exhibited 92.17% uptake compared to 53.66% for the aqueous extract and 80.79% for metformin, at a 100µg/ml glucose concentration. Statistical analysis (two-way ANOVA, P<0.05) confirmed the significance of results. The study indicated that silver nano-particles improved glucose utilization, potentially lowering blood glucose levels. Notably, nano-particles show superior anti-diabetic properties compared to the extract alone. Conclusion: The research underscored the potential of green synthesis through nano-particle technology in enhancing the therapeutic efficacy of natural remedies for diabetes, offering a promising avenue for developing more effective and safer treatments.